The Development of a Mini Dictionary Ibtikar Jadid in the Arabic Language Subject in Integrated Middle School - Zahro, Hasna Shofiatuz; Mukaromah, Muhimmatul (Institut Agama Islam Negeri Curup, 2024)
This research aims to make Arabic language learning more innovative and interesting. both methods and materials. Moreover, learning Arabic because it depends on mastering vocabulary. The aim achieved in this research is to find out how to develop a mini dictionary and determine the validity of the mini dictionary as a supporting book for Arabic language subjects by experts. This research uses a type of research and development which aims to develop both products and activities. According to Borg and Gall. The results of this scientific research are: This book is in the form of a mini dictionary, small in size and easy to carry. This book is designed for class VIII students who have vocabulary material that has not been included in the vocabulary table in the unit book. This “new innovation” mini dictionary has a very high level of validity. Based on the results of content material experts 98.21% and teaching method experts 94.11%. Both received very good marks, which indicates that this dictionary is suitable for use in learning.